Description of The Level of Knowledge and Periodontal Health Behavior Based on Nutritional Status in Universitas YARSI - Jihan Ar Rohim; Dewi Nurul Mustaqimah; Chaerita Maulani (Lembaga Penelitian Universitas YARSI, 2024)
Abstract Introduction: Research has investigated understanding and behaviors related to periodontal health maintenance and its health consequences. Failure to maintain periodontal health increases the likelihood of periodontal disease. Additionally, rising levels of obesity pose a risk for periodontal disease. Islam mandates its adherents to pursue knowledge in religious matters, which encompasses various aspects of life, including knowledge about maintaining health. Moreover, good behavior should be rooted in sound knowledge. Adequate knowledge and behaviors regarding oral health care promote cleanliness and healthiness of periodontal tissues. Objective: To determine the differences in knowledge and health behavior regarding periodontal health among students based on nutritional status. Material and Methods: This study used a cross-sectional method with a sample of 104 YARSI University students as respondents. The instrument used was a questionnaire containing 25 questions. The data analysis used was the Chi- Square categorical correlational analytical test. Results: The results of the Chi-Square test between knowledge of periodontal health care and nutritional status showed no significant relationship p = 0.378 (p>0.05). Meanwhile, between periodontal health behavior based on dental visits and nutritional status, there were significant results p = 0.035 (p<0.05). Discussion: Dental visit behavior based on BMI shows the same frequency between normal and obese respondents, this is not in line with previous research by Nihtila et al. (2016) which showed that people who are overweight tend not to visit the dentist in the last two years compared to people who are not overweight. Coclusion: 1) There is no correlation between awareness of periodontal health care and nutritional status, (2) Dental visit behavior correlates with nutritional status.